2019
DOI: 10.1111/ijpo.12521
|View full text |Cite
|
Sign up to set email alerts
|

Low‐calorie sweetener use, weight, and metabolic health among children: A mini‐review

Abstract: Summary A reduction in the consumption of added sugars and sugar‐sweetened beverages (SSBs) is a key focus of public health recommendations for a healthy diet among children. One approach to lower added sugar intake is to instead use low‐calorie sweeteners (LCSs), which contain no or few calories. Consumption of LCSs is increasing worldwide, with the most marked rise observed among children and adolescents. However, the extent to which LCS consumption is helpful or harmful for weight management is controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…A pattern has emerged in which observational studies make NNS's appear harmful causing increased weight, while intervention studies find NNS's reduce weight. A natural hypothesis was that in the observational studies the people consuming NNS's must have compensated by eating more solid food calories at subsequent meals, which indeed was found in some studies, but others reported a reduction in total energy expenditure after NNS consumption [81]. When sweet receptors in the oral cavity are activated not only does the brain perceive sweetness but the body prepares to digest calories through the cephalic phase responses, most notably the cephalic phase insulin response (CPIR) which is a neurally-mediated release of insulin prior to nutrient absorption [82].…”
Section: Nutrient Sensingmentioning
confidence: 96%
“…A pattern has emerged in which observational studies make NNS's appear harmful causing increased weight, while intervention studies find NNS's reduce weight. A natural hypothesis was that in the observational studies the people consuming NNS's must have compensated by eating more solid food calories at subsequent meals, which indeed was found in some studies, but others reported a reduction in total energy expenditure after NNS consumption [81]. When sweet receptors in the oral cavity are activated not only does the brain perceive sweetness but the body prepares to digest calories through the cephalic phase responses, most notably the cephalic phase insulin response (CPIR) which is a neurally-mediated release of insulin prior to nutrient absorption [82].…”
Section: Nutrient Sensingmentioning
confidence: 96%
“…Exposing children to sugars or NNS might reinforce sweet preferences that could persist for their lifetime 15 and lead to overconsumption of sugar‐sweetened foods and beverages 16 . Furthermore, the consumption of some NNS has been associated with gut microbiota alterations, metabolic syndrome and higher body mass index, but results are inconclusive in paediatric population 14,16–18 . In addition, children are at risk of surpassing the limits for safe NNS intake because the acceptable daily intake (ADI) is calculated based on body weight, and children have lower body weight than adults 9…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, the consumption of some NNS has been associated with gut microbiota alterations, metabolic syndrome and higher body mass index, but results are inconclusive in paediatric population. 14,[16][17][18] In addition, children are at risk of surpassing the limits for safe NNS intake because the acceptable daily intake (ADI) is calculated based on body weight, and children have lower body weight than adults. 9 Chile is one of the few countries where eight different NNSs must be quantified on the nutrition facts panel (NFP).…”
mentioning
confidence: 99%
“…Sugary drinks taxation appears as one of the most promising prevention programs according to modeling studies and it can be of more impact if associated with other interventions enabling access to healthy foods [ 85 , 86 ]. Another approach is the use of low-calorie sweeteners that contain no or few added sugars that have been associated with contrasting results [ 87 ].…”
Section: Introductionmentioning
confidence: 99%